Effects of leucine supplementation and serum withdrawal on branched-chain amino acid pathway gene and protein expression in mouse adipocytes. - Abderrazak Kitsy; Skyla Carney; Juan C Vivar; Megan S Knight; Mildred A Pointer; Judith K Gwathmey; Sujoy Ghosh (PLoS ONE)
The essential branched-chain amino acids (BCAA), leucine, valine and isoleucine, are traditionally associated with skeletal muscle growth and maintenance, energy production, and generation of neurotransmitter and gluconeogenic precursors. Recent evidence from human and animal model studies has established an additional link between BCAA levels and obesity. However, details of the mechanism of regulation of BCAA metabolism during adipogenesis are largely unknown. We interrogated whether the expression of genes and proteins involved in BCAA metabolism are sensitive to the adipocyte differentiation process, and responsive to nutrient stress from starvation or BCAA excess. Murine 3T3-L1 preadipocytes were differentiated to adipocytes under control conditions and under conditions of L-leucine supplementation or serum withdrawal. RNA and proteins were isolated at days 0, 4 and 10 of differentiation to represent pre-differentiation, early differentiation and late differentiation stages. Expression of 16 BCAA metabolism genes was quantified by quantitative real-time PCR. Expression of the protein levels of branched-chain amino acid transaminase 2 (Bcat2) and branched-chain alpha keto acid dehydrogenase (Bckdha) was quantified by immunoblotting. Under control conditions, all genes displayed induction of gene expression during early adipogenesis (Day 4) compared to Day 0. Leucine supplementation resulted in an induction of Bcat2 and Bckdha genes during early and late differentiation. Western blot analysis demonstrated condition-specific concordance between gene and protein expression. Serum withdrawal resulted in undetectable Bcat2 and Bckdha protein levels at all timepoints. These results demonstrate that the expression of genes related to BCAA metabolism are regulated during adipocyte differentiation and influenced by nutrient levels. These results provide additional insights on how BCAA metabolism is associated with adipose tissue function and extends our understanding of the transcriptomic response of this pathway to variations in nutrient availability.